2000
DOI: 10.1016/s0002-9440(10)64768-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanisms and Kinetics of Apoptosis Induced by Microinjection of Cytochrome c in Rat Kidney Tubule Epithelial Cells (NRK-52E)

Abstract: Recent reports substantiating the role of cytochrome c in the induction of apoptosis led us to examine the kinetics and mechanisms involved in this process as an extension of our ongoing studies of cell injury and cell death. Microinjection of cytochrome c into NRK-52E kidney cells produced rapid apoptosis, which usually began within 30 minutes and reached a maximum of 60 -70% by 3 hours. The changes that occurred included four phases: an initial shrinkage phase, an active phase, a spherical phase, and a necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…These systematic changes were entirely different from those seen in oncotic cardiomyocytes, in which myofibrils were supercontracted and exhibited contraction bands with preserved Z disks. Ca 2ϩ transients appear to be related to the dynamics of apoptosis ubiquitously observed among various cell types (3,9,23,24). These dynamics would be especially apparent in the beating of cells with well-developed myofilament systems, e.g., adult cardiomyocytes, although they would also be reflected in the proteolysis and DNA fragmentation catalyzed by Ca 2ϩ -dependent protease and DNases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systematic changes were entirely different from those seen in oncotic cardiomyocytes, in which myofibrils were supercontracted and exhibited contraction bands with preserved Z disks. Ca 2ϩ transients appear to be related to the dynamics of apoptosis ubiquitously observed among various cell types (3,9,23,24). These dynamics would be especially apparent in the beating of cells with well-developed myofilament systems, e.g., adult cardiomyocytes, although they would also be reflected in the proteolysis and DNA fragmentation catalyzed by Ca 2ϩ -dependent protease and DNases.…”
Section: Discussionmentioning
confidence: 99%
“…Video recording of various apoptotic cell types in culture has revealed apoptosis to be a dynamic process that is complete within hours and is characterized by several common features: cellular shrinkage and rounding, budding or blebbing, and apoptotic body formation (3,23,24). These structural changes are accompanied by disassembly of the cytoskeletal and nuclear scaffold as a result of proteolysis catalyzed by caspase family proteases (25,36).…”
mentioning
confidence: 99%
“…In one case, results from non-quantitative, direct fluorescence microscopic examination of cells stained with a fluorescent, potential-sensitive mitochondrial dye were interpreted as indicating that cytosolic cytochrome c had no effect on mitochondrial polarization. 14 In the second case, it was reported that loss of mitochondrial membrane potential (DC mit ) did not occur until immediately before cell death induced by microinjection of cytochrome c. 17 However, the validity of the technique used in this study to measure changes in DC mit (staining cells with rhodamine 123) was questioned in recent reports. 18,19 Thus, it remains uncertain whether, in intact cells, the release of cytochrome c to the cytosol triggers quantitative changes in mitochondrial polarization or other mitochondrial changes.…”
Section: Introductionmentioning
confidence: 90%
“…TSP-1 at 1 µg/ml was added to cultured kidney proximal tubule (NRK) cells and studied at 24 and 48 hours for evidence of apoptosis by cytochrome c release and caspase-3 activity. The NRK-52E normal kidney cell line is derived from the proximal tubule epithelium (PTE) of the rat kidney, is nontumorigenic, retains many morphological and physiological characteristics of PTE, and has been used to mimic changes in vivo (31)(32)(33). Cytochrome c apoptosis detection kit (Alexa Fluor 488 assay; Invitrogen Corp.) was used to perform the apoptosis assay.…”
Section: Kidney Ir Injury: Animal Model Kidney Ir Injury Was Inducedmentioning
confidence: 99%